Research Progress on the Mechanism of Cochlear Hair Cell Regeneration - Xu, Shan; Yang, Ning (Frontiers in Cellular Neuroscience, 2021)
Mammalian inner ear hair cells do not have the ability to spontaneously regenerate, so their irreversible damage is the main cause of sensorineural hearing loss. The damage and loss of hair cells are mainly caused by factors such as aging, infection, genetic factors, hypoxia, autoimmune diseases, ototoxic drugs or noise exposure. In recent years, research on the regeneration and functional recovery of mammalian auditory hair cells has attracted more and more attention in the field of auditory research. How to regenerate and protect hair cells or auditory neurons through biological methods and rebuild auditory circuits and functions are key scientific issues that need to be resolved in this field. This review mainly summarizes and discuss the recent research progress in gene therapy and molecular mechanisms related to hair cell regeneration in the field of sensorineural hearing loss.